(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Information and communication technology (ICT) have been become vital tool in providing nursing care to patient in the hospital and after patient discharge. ICT empower nurses with information and different needs to improve quality of nursing care. Aim of the study: Assess the relation between information and communication technologies (ICT), and empowerment of nurses at Alahrar Teaching Hospital. Subjects and method: Research Design: An exploratory, descriptive research design was utilized at this study. Setting: This study was carried out at Alahrar Teaching Hospital which affiliated to the general organization for Teaching Hospitals and institutes. Subjects: Random sample from nurses(236) was concluded from previous mentioned setting. Tool of data collection: Adapted information and communication technologies (ICTs) questionnaire, Psychological empowerment scale& Adapted Conditions for Work Effectiveness Questionnaire (CWEQ). Results: More than two thirds 67.8% of the studied nurses had moderate level regarding perception of ICT, majority 94.1% &89.4% of them had moderate level regarding to staff nurses' structured and psychologically empowerment respectively. Conclusion: There was a strong role for information and communication technologies (ICT), in improving structured empowerment and psychological empowerment among studied nurses in the working setting. Recommendation: Establish training program for staff nurses about using information and communication technology devices, also provide different supplies, equipment and work information for staff nurses that improve their structural empowerment.